COLLABORATIVE MANAGEMENT OF HANDLING WASTE IN DOULU TOURISM AREA OF KARO REGENCY - Brian Pratama Depari (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
Located in Doulu Village of Karo Regency of Sumatera Utara, Penatapen tourist area is one of the tourist attractions that have the potential to generate waste. Proper waste generation handling is needed to be implemented to increase the quality of services. The role of visitors, entrepreneurs and government are crucial to improving the waste management system. Based on observations, waste management has not reached optimal conditions. The community is less aware of sorting out waste and does not have adequate bins. This research analyzed waste generation and evaluate the opportunities for collaborative management in handling waste generation in Penatapan tourist area. The analysis results in the determination collaborative management strategies are carried out by SWOT method. Observation is taken within 16 days during the national holiday. The waste generation reached 1046,7 kg of waste. SWOT analysis obtained the right strategy of processing waste from its source by making a bins with the appropriate volume referring to SNI 19-2454-2002. The proposed collaborative waste management strategy is government to educate the community to sort out waste independently and be aware of environmental issues as well as pilot village programs with the main activities of processing organic waste into fertilizer in Doulu Village.